Shrub facilitation of Quercus ilex and Quercus pubescens regeneration in a wooded pasture in central Sardinia (Italy) - Alias, S; Bianchi, L; Calamini, G; Gregori, E; Sioni, S (iForest - Biogeosciences and Forestry)
In the woodlands of Sardinia, as in many other areas of the Mediterranean region, grazing of domestic animals is still very common, though often in the absence of any sustainable management logic or technique. The present work analyzes the effects of excessive grazing pressure on a wooded pasture in the municipality of Orgosolo (Nuoro province), emphasizing the effects on the natural regeneration of the oak species (Quercus ilex and Quercus pubescens). This study has revealed the positive effects of the interaction between shrubs and seedlings of tree species. Crataegus monogyna proved to be the most efficient shrub species in favouring the establishment and growth of saplings; Rubus ulmifolius is efficient in the establishing phase but somewhat less so in the following stages. The other shrub species (Prunus spinosa, Genista pichi-sermolliana, Stachys glutinosa) play a lesser facilitating role. Despite the fact that seedlings are found in more than half (56%) of the shrub patches, the average age of the seedlings (140.6 yrs) and their small average size (height 241.4cm) lead to think that the present grazing pressure is incompatible with any concrete chance of success for their natural regeneration.
Keywords: Overgrazing; Quercus ilex; Quercus pubescens; Shrub facilitation; Tree regeneration; Wood pasture management